Body Composition in Elderly People in Telagah Village - Fitriyani Nasution; Meriza Martineta; Dina Keumala Sari; Nenni Dwi Aprianti Lubis; Zaimah Z Tala; Murniati Manik (Buletin Farmatera, 2023)
Abstract: The elderly population is expected to nearly double in decades. The elderly is associated with increased malnutrition, decreased muscle and bone mass, decreased water volume in the body, and increased body fat mass. This research aims to determine the body composition of the elderly in Telagah Village to improve their degree of health. This study used a cross-sectional design and sampling method using total sampling conducted in conjunction with counselling. The inclusion criteria for research subjects are ≥ 60 years old and willing to participate in research. Researchers directly measured participants to obtain the necessary data in the form of age, sex, height, weight, body mass index, body fat percentage, total body fluid percentage, visceral fat, and bone mass. The collected data is presented in the form of frequency and percentage. The total participants in this study were 30 people, the majority of whom were women (80%), age range 60-69 years (76.67%), and had nutritional status in the form of obesity (66.7%). The average height and weight of the participants were 152.85 ± 8.41 cm and 62.75 ± 14.02 kg. From body composition data, the majority of participants had a high percentage of body fat (46.7%), low bone mass (93.3%), normal visceral fat (86.7%), and normohydration (56.7%). The majority of nutritional status in the elderly in the study was obese with body composition that had a high percentage of body fat, low bone mass, normal visceral fat, and normohydration.